Ovarian malignant mixed germ cell tumor. A case report - Pérez-Ortiz, Viorkis (2020)
Ovarian malignant germ cell tumors, although rare, are the most common type of malignant ovarian neoplasms in girls and adolescents; approximately two thirds of all cases occur in women under 20 years old. These tumors represent 2%-5% of all ovarian germinal tumors. Tumors comprise two or more types of germ cell components that include dysgerminoma accompanied by tumors of the endodermal sinus, embryonal cell carcinoma, mature or immature teratoma and/or choriocarcinoma. There are few case reports of mixed germ cell tumors with different combinations of malignant components. Alpha-fetoprotein and human chorionic gonadotropin are the most characteristic tumor markers, and immunohistochemical findings are important in the diagnosis of mixed malignant ovarian germ cell tumors. Surgery plus adjuvant chemotherapy is the first option to preserve fertility in any girl or adolescent who presents a rapidly growing pelvic tumor with high concentrations of alpha-fetoprotein or human chorionic gonadotropin. We present a case of ovarian malignant mixed germ cell tumor.